Penafsiran Al-Qur’an Perspektif Gus Dur dalam Buku Islam Ku, Islam Anda, Islam Kita - Syafri Fajarwanto (Syariati: Jurnal Studi Al-Qur'an dan Hukum, 2022)
The interpretation of the modern-contemporary period focuses its interpretation on efforts to position the Qur'an as a book of guidance for humans, namely by prioritizing the "initial use" aspect of the Qur'an , namely to provide solutions to the concrete problems faced by Muslims. present time. There are not a few Indonesian national figures who have initiated Islamic reformist thoughts without leaving the historical and socio-cultural context that surrounds the Indonesian nation. One of these figures is KH. Abdurrahman Wahid or familiarly called Gus Dur. Although he did not leave much in the field of interpretation of the Qur'an, but it fulfills a number of aspects that are worthy and interesting to study. This research is completely methodological in the form of library research , namely a research system that uses data and information from various kinds of materials and literature. Like most character studies , this research uses qualitative research. Results from study this namely Gus Dur more many interpret verses of the Koran with use method ijmāli (global) and use ra`yu or analysis and his thoughts as source interpretation. However, there are sometimes Gus Dur use other verses of the Koran as well as hadith as source in interpreting the Qur'an, no seldom method interpretation thematic also used. Gus Dur's interpretation of Islamic verses and justice are still relevant to the current condition of society, which requires a role model in understanding the meaning of "justice" brought about by the Qur'an.